Selection and characterization of single domain antibodies against human CD20. (October 2016) - Liu, Jinny L.; Zabetakis, Dan; Goldman, Ellen R.; Anderson, George P.
Highlights: A llama immune phage display library against human Hoc-CD20 fusions was constructed. Class A sdAbs shown 40 fold and higher affinity to Hoc-CD20 than Hoc were obtained through subtractive bio-panning. Some of class A sdAbs bound to full length of CD20 on SU-DHL-4 cells. Abstract: CD20 is a membrane protein with four integral membrane regions and a large extracellular loop between residues 142 and 187, which serves as a target binding region for rituximab (RTX) and most other anti-CD20 monoclonal antibodies. It is highly expressed in B-lymphoma cells and B lymphocytes and often serves as a target for immunotherapy. In this study, we developed single domain antibodies (sdAbs) for the sensitive detection of CD20. To achieve this, an immune sdAb library was prepared from llamas immunized with a fusion between the large loop from CD20 and Hoc, a highly antigenic protein from the T4 bacteriophage, (CD20-Hoc). By subtracting binders to recombinant Hoc during the biopanning, potential anti-CD20 sdAbs were selected, sequenced, and characterized for their binding affinity to CD20-Hoc fusion versus Hoc. Twenty five clones grouped into three different families based on CDR3 sequence were identified as potential CD20 binders. The binding kinetics of representative sdAbs from each class and RTX were evaluated by surface plasmon resonance (SPR). Most of the sdAbs that were evaluated show binding affinities to CD20-Hoc in the nM range, and class A sdAbs, exhibited ≥40-fold increase in affinity for CD20-Hoc versus Hoc. When the binding of the sdAbs to CD20 on SU-DHL-4 cells was evaluated by flow cytometry, only class A sdAbs displayed strong binding to CD20 and recognized DHL cells in a concentration dependent manner.